SISTEM INFORMASI HOUSEKEEPING BERBASIS WEB DI HOTEL PRAOE LAJAR TEGAL - Tofik Firmansyah; Rudi Heryanto (Computer Based Information System Journal, 2026)
This study aims to develop and evaluate a web-based Housekeeping Management Information System to improve the effectiveness of room status management at Praoe Lajar Hotel, Tegal. The research employed a Research and Development (R&D) method using the Prototype development model with a mixed-methods approach. The system was developed using Visual Studio Code and integrated with the cloud database platform Firebase to enable real-time data updates. Data were collected through observation, Likert-scale questionnaires, and interviews involving 15 respondents consisting of hotel administrators, housekeeping staff, and operational managers. Data analysis included validity and reliability tests, classical assumption tests, and regression analysis using SPSS. The results indicate that information system quality has a positive and significant effect on system effectiveness, with a significance value of 0.000 and a coefficient of determination (R²) of 0.949. This finding indicates that 94.9% of the system’s effectiveness is influenced by system quality, which includes technical quality, data integration, accessibility, and security. In addition, interview results reveal that the system improves work efficiency, reduces recording errors, and supports employee productivity through real-time room status updates. Therefore, the developed system has proven effective in enhancing operational coordination and improving the management quality of hotel housekeeping.